Why did Aceh lose its Nineteenth Century Independence? Comparisons with Siam and other states - Anthony John S. Reid (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2016)
By the middle of the 19th century fully independent states in Southeast Asia were few, and all felt threatened by the advance of competitive European imperialisms. By 1900 only Siam (Thailand) had retained its full formal independence, though arguably by yielding key levers of control to the British. Siam’s success is often compared with the failure of Burma and Viet Nam, conquered by Britain and France respectively in the late 19th century.  Archipelago states have seldom entered this comparison, although Aceh had unique advantages in the ability to play off British and Dutch. The argument here is that the Aceh leadership did have vital agency, and made some crucial choices that could be considered mistakes from a Siam perspective. Dutch and British choices and mistakes have been better studied, but Acehnese ones also deserve to be.